De libertate et servitute spiritus: Pneumatologie in Luthers Freiheitstraktat - Dietz, Martin Timóteo (Forschungen zur systematischen und ökumenischen Theologie, 2015)
Martin Dietz Timoteo deals with the question, how important the Holy Spirit in Luther's "Tractatus de libertate christiana". His goal is to prove that Luther's treatise on freedom, "particularly palpable in its Latin version, eminently pneumatological character possesses. Although the "freedom treatise" unfolds no running pneumatology, however, describes Christian life as a pneumatic experience. Through the Scriptures, especially the Pauline writings, Luther is passed to the main insights of the treatise. -- Inspired by the apostles, Luther describes a continuous downward movement. Faith receives the fruit of God coming down to man in his Son. The love is experienced by faith the righteousness of God continue their neighbor and is thereby involved in God's Kondeszendenzhandeln. However, the acting in love faith is not a human possibility, but a Spirit-wrought experience that is best described as "pneumatologia crucis". -- Martin T. Dietz manages to trace the pneumatic character of Christian existence as ministering freedom or cross theological profile highlight of Luther pneumatologischem thinking in the "Freedom Scripture